“INFLUENCE OF SWISS BALL TRAINING ON MENOPAUSE SPECIFIC QUALITY OF LIFE” - BenedineD’souza, Philomena; Varadharajulu, G. (International Journal of Psychosocial Rehabilitation, 2020)
Swiss ball is also known as the physio-ball, stability ball, pilates-ball, exercise balls, wellness ball, fit-ball, and gym-ball. Swiss ball training improves nervous-system function that results in functional strength gains. To find the influence of Swiss ball training on Menopause-specific Quality of life. Clinical trial was conducted on Menopausal women. . The present study was conducted with 32 samples, including 16 menopause transitional females in group A and 16 menopausal females in group B. subjects was selected Simple random sampling method. Study was conducted at Out Patient Department of Krishna College of Physiotherapy, Karad. The subjects outcome was seen on MENQOL questionnaire filled again post treatment at the end of 6 weeks. The core strength was assessed by double leg lowering test and multifidus test. The training lasted for 6 weeks. extreme significant difference between the age of menopausal transitional of group A and post menopause females in group B. (t value=11.687, P value=0.0001).Pre and Post values of Group A and B were compared by applying Mann Whitney test. Pre treatment shows significant difference (U=72.000, P= 0.0338) in the multifidus grading system, whereas post treatment shows significant difference (U=67.000, P= 0.0208 sum of ranking in group A= 325.00 and B=203.00). Swiss ball training has influence in improving the Menopause-specific quality of life and core muscle strength in menopausal women.